GROWTH PERFORMANCE AND SERUM BIOCHEMICAL PROFILE OF CROSSBRED (LWY X DESI) ENTIRE MALE PIGS FED SHEANUT CAKE DIETS - D. Sudeesh; J. Suresh; A. Ravi; S.Sreedhar; J.V. Ramana (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was undertaken on 24 crossbred pigs to study the effect of different levels of sheanut cake (SNC) by replacing deoiled rice bran (DORB) (T1-0%, T2-50%, T3-75% and T4-100%) on growth performance and serum biochemical profile of crossbred (Large White Yorkshire X Desi) entire male pigs. There was a significant (P<0.01) increase in the number of days to reach the target weight, average daily gain, feed consumed per day and feed consumed per kg weight gain increased gradually as the level of SNC increased in the diets. The SGOT, SGPT and serum total protein levels were within the normal range while the total cholesterol levels were less than the normal range in pigs fed on diets containing 75% and 100% replaced DORB with sheanut cake and the values were 32.70 , 30.59 g/dl. The study showed that feeding of sheanut cake did not have any effect on the serum levels of SGOT, SGPT, total protein levels but the total cholesterol level will be less than the normal level.